The GPR55 antagonist CID16020046 protects against intestinal inflammation. Issue 10 (30th July 2015) - Stančić, A.; Jandl, K.; Hasenöhrl, C.; Reichmann, F.; Marsche, G.; Schuligoi, R.; Heinemann, A.; Storr, M.; Schicho, R.
Abstract Background G protein‐coupled receptor 55 (GPR55) is a lysophospholipid receptor responsive to certain cannabinoids. The role of GPR55 in inflammatory processes of the gut is largely unknown. Using the recently characterized GPR55 inhibitor CID16020046, we determined the role of GPR55 in experimental intestinal inflammation and explored possible mechanisms of action. Methods Colitis was induced by either 2.5% dextran sulfate sodium (DSS) supplemented in the drinking water of C57BL/6 mice or by a single intrarectal application of trinitrobenzene sulfonic acid (TNBS). Key Results Daily application of CID16020046 (20 mg/kg) significantly reduced inflammation scores and myeloperoxidase (MPO) activity. In the DSS colitis model, levels of tumor necrosis factor alpha (TNF‐α) and interleukin 1 beta (IL‐1β), and the expression of cyclooxygenase (Cox)‐2 and signal transducer and activator of transcription 3 (STAT‐3) were reduced in colon tissues while in TNBS‐induced colitis, levels of Cox‐2, IL‐1β and IL‐6 were significantly lowered. Evaluation of leukocyte recruitment by flow cytometry indicated reduced presence of lymphocytes and macrophages in the colon following GPR55 inhibition in DSS‐induced colitis. In J774A.1 mouse macrophages, inhibition of GPR55 revealed reduced migration of macrophages and decreased CD11b expression, suggesting that direct effects of CID16020046 on macrophages may have contributed to the improvement of colitis. GPR55−/− knockout mice showed reduced inflammation scores as compared to wild type mice in the DSS model suggesting a pro‐inflammatory role in intestinal inflammation. Conclusions & Inferences Pharmacological blockade of GPR55 reduces experimental intestinal inflammation by reducing leukocyte migration and activation, in particular that of macrophages. Therefore, CID16020046 represents a possible drug for the treatment of bowel inflammation.